Integrity & Accountability Commissions of Inquiry: A South African Perspective - Lauren Kohn (Utrecht Law Review)
Corruption – and the organized crime that it enables – is a major impediment to the attainment of peace, justice and sustainable development. The Judicial Commission of Inquiry into State Capture in South Africa (the ‘Zondo Commission’) provides a powerful illustration of how such malfeasance can unravel the state-societal fabric, causing deep-seated conflict between state and citizen. More positively, however, the Zondo Commission also reveals the irreplicable curative properties of commissions of inquiry as part of a ‘just institutional approach to conflict prevention and resolution’. This is especially so where they deal properly with matters of public concern and, in particular, the integrity and accountability of public power. In my article, I argue for the recognition of such commissions of inquiry as part of South Africa’s ‘integrity and accountability’ (I&A) fourth branch of state. My argument is made against the backdrop of an account of the state, and thus constitutionalism, that is positive in nature insofar as it focuses on the state’s role in (pro)actively advancing the public interest. Giving proper recognition to I&A Commissions in the nature of the Zondo Commission will in turn enhance their remedial powers and effectiveness. In light of these arguments, I encourage the implementation of the Zondo Commission recommendation that a ‘permanent anti-state capture and corruption commission’ be provided for in Chapter 9 of the South African Constitution.